Association Between Lung Parenchymal Attenuation in Computed Tomography and Airflow Limitation in Adults with Cystic Fibrosis - Lucía Esteban Baloira; Ester Zamarrón de Lucas; Carlos Carpio Segura; Macarena Lerín Baratas; María Fernández Velilla; María Isabel Torres Sánchez; Inmaculada Pinilla Fernández; Pablo Mariscal Aguilar; Rodolfo Álvarez-Sala Walther; Concepción Prados Sánchez (Diagnostics)
Objectives: To determine the association between airflow limitation and the quantification of lung attenuation in computed tomography (CT) in adult patients with cystic fibrosis (CF). Methods: A cross-sectional study in a single center between January 2013 and December 2018 in adult patients with stable CF. We collected clinical data and the results of spirometry and plethysmography. A chest CT at inspiration and expiration, using a specific software that automatically measured the lung attenuation, was performed. Results: In total, 73 patients (63% males) were included. The mean age was 31.6 ± 12.3 years and the FEV1 was 67.8 ± 25.9% pred. An airflow limitation was found in 63%, the mean residual volume was 159.9% pred, and air trapping was observed in 50 (87.7%) of the patients. The patients with airflow limitations showed a higher bulla index and a percentage of lung voxels in the range of emphysema. The FEV1 and the FEV1/FVC correlated with the percentage of the lungs at a high attenuation value (HAV), the range of emphysema, and the bulla index at inspiration, as well as the mean lung density at expiration and the inspiratory–expiratory variation of the mean lung density (MLDi-e). Finally, in the multivariate model, the MLDi-e and the HAV at inspiration were associated with airflow limitations. Conclusions: The measurements obtained from the automated quantification of lung parenchymal attenuation predicts airflow limitation in CF.